Self-harm and suicide in adolescents. - Hawton, K; Saunders, K; O'Connor, R (2012)
Self-harm and suicide are major public health problems in adolescents, with rates of self-harm being high in the teenage years and suicide being the second most common cause of death in young people worldwide. Important contributors to self-harm and suicide include genetic vulnerability and psychiatric, psychological, familial, social, and cultural factors. The effects of media and contagion are also important, with the internet having an important contemporary role. Prevention of self-harm and suicide needs both universal measures aimed at young people in general and targeted initiatives focused on high-risk groups. There is little evidence of effectiveness of either psychosocial or pharmacological treatment, with particular controversy surrounding the usefulness of antidepressants. Restriction of access to means for suicide is important. Major challenges include the development of greater understanding of the factors that contribute to self-harm and suicide in young people, especially mechanisms underlying contagion and the effect of new media. The identification of successful prevention initiatives aimed at young people and those at especially high risk, and the establishment of effective treatments for those who self-harm, are paramount needs.